Culvating Rule-Abiding Behavior through Digital-Age Civic Education in Elementary Schools - Farel Alfina Silvasashi; S Sutama (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Student rule compliance has become an inscreasingly important issue in the digital era. Civic Education learning should emphasize the cultivation of rule-abiding behavior. This article has two research objectives. 1) To describe the cultivation of rule-abiding behavior in the classroom in digital-age civic education learning among fifth-grade elementary school students. 2) To explore the cultivation of rule-abiding behavior in schools in digital-age civic education learning among fifth-grade elementary school students.Methodology: This is a qualitative-ethnographic study. The research subjects were the principal, civic education teachers, and fifth-grade student of State Elementary School 3 Tanggan, Sragen. Data collection methods included interviews, observation, and document analysis. Data validity was obtained through triangulation of sources and methods. Data analysis was conducted inductively.Results: The result of the study show that 1) students began to reflect an attitude of obedience to class rules through habituation strategies, teacher role modeling, and the use of digital media. 2) Students who were guided using a contextual approach and the use of school social media successfully increased their awareness and active participation in obeying school rules.Applications/Originality/Value: This research in its qualitative ethnographic approach, which allows researvhers to directly observe interactions, habits, and the culture of student compliance in the context of Civic Eduvation learning in the digital age.